Relationship between academic procrastination and internet addiction in Peruvian university students: the mediating role of academic self-efficacy - Chavez-Yacolca, Dana Rocio; Castro-Champión, Ruth Beatriz; Cisneros-Gonzales, Nely Marlene; Cunza-Aranzábal, Denis Frank; Morales-García, Mardel; Abanto-Ramírez, Carlos D. (Frontiers in Psychology, 2025)
IntroductionThis study evaluated the mediating role of academic self-efficacy in the relationship between internet addiction and academic procrastination among Peruvian university students.MethodA cross-sectional explanatory design was employed with a convenience sample of 334 participants. Instruments used included the Specific Perceived Self-Efficacy Scale of Academic Situations (EAPESA), the Lima Internet Addiction Scale (EAIL), and the Academic Procrastination Scale (APS). The reliability and internal structure of each scale were verified, and the EAIL was validated. Descriptive analysis and correlation between variables were conducted, followed by path and mediation analyses.ResultsInternet addiction significantly negatively affected academic self-efficacy (β = −0.381, t = −4.52, p < 0.001). Academic self-efficacy negatively impacted academic procrastination (β = −0.522, t = −7.04, p < 0.001). Internet addiction positively affected academic procrastination (β = 0.642, t = 5.72, p < 0.001). The total effect of internet addiction on academic procrastination and academic self-efficacy was significant (β = 0.841, t = 7.17, p < 0.001). Academic self-efficacy partially mediates the relationship between internet addiction and academic procrastination, suggesting universities should implement strategies to enhance academic self-efficacy in students.